PENINGKATAN PEMAHAMAN TAJWID SISWA KELAS VIII 4 MELALUI STRATEGI COOPERATIF LEARNING DI TPQ SMPN 13 BINTAN - Zulkifli Zulkifli (Jurusan Tarbiyah dan Pendidikan, 2021)
The method has a very significant position in achieving the goals of Islamic education, therefore, the application of the right method greatly influences the success in the teaching and learning process. On the other hand, errors in implementing the method will be fatal. In the tajwid material, student learning outcomes at SMPN 13 Bintan are classified as low. This can be seen from the results of the assessment carried out by the teacher during grade VIII which stated that students who scored below the Minimum Completeness Criteria) were more than 50%. To solve this problem, try to find a solution to improve the learning outcomes of tajwid material by using the